Diversity, Spatial Distribution, Breeding Status, Production Level, and Use Dynamics Analysis of Food Barley in Ethiopia - Asaye Demelash; Mastewal Alehegn; Ahadu Menzir (Advances in Agriculture)
Barley is a significant cereal crop in Ethiopia, known for its rich genetic diversity, which includes both hulled and hull-less types adapted to the diverse agroecological zones of the country. This diversity is crucial for breeding programs aimed at developing improved varieties that can withstand various stresses. The spatial distribution of barley in Ethiopia is extensive, from the highlands to midaltitude areas, with the crop particularly well-suited to the cool and moist conditions found in the highlands. Barley breeding in Ethiopia has made significant progress, with the Ethiopian Institute of Agricultural Research (EIAR) and other institutions focusing on traits such as disease resistance, drought tolerance, and improved grain quality. Barley production in Ethiopia is substantial, with the crop grown both for food and feed. It faces challenges such as low productivity, limited access to improved varieties and inputs, and the impact of climate change. Despite these challenges, barley plays a vital role in food security, income generation, and cultural practices. The use dynamics of barley in Ethiopia are varied, with traditional uses including the production of injera, beer, and other food products. There is also an increasing interest in barley for its potential in the production of malt for the brewing industry and as a source of high-quality protein for animal feed. Finally, barley is an important cereal crop in Ethiopia, with significant genetic diversity, spatial distribution across various altitudes, breeding progress toward improved varieties, production challenges and opportunities, and diverse uses in food, feed, and industry. Ongoing research and development efforts are essential to enhance the productivity and sustainability of barley in Ethiopia for the current and future.